COMPREHENSIVE STUDY OF OVERCLAIM SKINCARE PRODUCTS (LEGAL AND HEALTH PERSPECTIVES) - Khulaili Harsya, Rabith Madah; Muhammad Salman Alfansuri Jacob; Untung Gunawan; Rudi Rahman; Dita Dismalasari Dewi (JURNAL ILMIAH EDUNOMIKA, 2025)
ABSTRACT This study is a qualitative study with a descriptive approach that will study Skincare Overclaim from three perspectives, namely Consumer Protection Law, Health, and Social. The data used in this article is primary data that researchers obtained from secondary sources in the form of scientific articles, books, scientific magazines, and various other sources. The data obtained were analyzed by stages of data collection, data selection, data reduction. The conclusion in this articcle show that the skincare overclaim action violates the second and third rights of consumers, namely to obtain goods according to the composition promised and honestly and the owner must be held absolutely responsible for complying with the provisions in the civil law book. From a health perspective, overclaim skincare does not have a significant impact on consumers if it does not contain dangerous ingredients. Keywords: Overclaim, Skincare, Legal, Health